2016
DOI: 10.1021/acsnano.6b05952
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale-Barrier Formation Induced by Low-Dose Electron-Beam Exposure in Ultrathin MoS2 Transistors

Abstract: Utilizing an innovative combination of scanning-probe and spectroscopic techniques, supported by first-principles calculations, we demonstrate how electron-beam exposure of field-effect transistors, implemented from ultrathin molybdenum disulfide (MoS), may cause nanoscale structural modifications that in turn significantly modify the electrical operation of these devices. Quite surprisingly, these modifications are induced by even the relatively low electron doses used in conventional electron-beam lithograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 37 publications
3
31
0
Order By: Relevance
“…This in turn provides favorable conditions for the observation of negative differential conductance, by suppressing the likelihood of carriers being transferred into the T valleys at low fields 4 In our simulations, we have systematically raised the T valleys and find that negative differential conductance begins when the inter-valley separation (Δ) is as little as 100 meV (i.e. when it is increased by just 25% relative to the unstrained case), corresponding to a strain level of just 1% 31 , 32 This estimate is consistent with recent scanning-microscopy studies of MoS 2 FETs, which have revealed the presence of unintended strain in their channels, introduced during nanofabrication 33 By assuming Δ = 110 meV, in Fig. 3(b) we compute the fraction of the carriers that remain in the K valley as a function of the electric field.…”
Section: Resultssupporting
confidence: 85%
“…This in turn provides favorable conditions for the observation of negative differential conductance, by suppressing the likelihood of carriers being transferred into the T valleys at low fields 4 In our simulations, we have systematically raised the T valleys and find that negative differential conductance begins when the inter-valley separation (Δ) is as little as 100 meV (i.e. when it is increased by just 25% relative to the unstrained case), corresponding to a strain level of just 1% 31 , 32 This estimate is consistent with recent scanning-microscopy studies of MoS 2 FETs, which have revealed the presence of unintended strain in their channels, introduced during nanofabrication 33 By assuming Δ = 110 meV, in Fig. 3(b) we compute the fraction of the carriers that remain in the K valley as a function of the electric field.…”
Section: Resultssupporting
confidence: 85%
“…MoS 2 layers can be significantly activated, functionalized, and modified. The irradiation-induced defects are beneficial for several applications including: solar cells [19,[194][195][196], batteries [54,197,198], supercapacitors [199], thin film transistors [15,16,80,86,110,138,[200][201][202][203][204][205], sensors [17,55,56,106,[206][207][208][209][210], hydrogen generators [8,47,50,69,134,176,177,183,211,212], and applications in thermoelectrics [213][214][215][216], piezotronics [63], valleytronics [65], and environments [45,49]. MoS 2 2D layers were damaged simultaneously under ...…”
Section: Discussionmentioning
confidence: 99%
“…To understand the irradiation-induced defects well, the synthesis/preparation details of the as-prepared MoS 2 layers will be described in each section in addition to irradiation. [75] mono-layer electron 60 keV 10 6 -10 9 electron /nm 2 STEM beam 400-700 • C in vacuum induced 2H/1T phase transition [76] ∼10 layer electron 3-15 keV n/a EPMA in vacuum broke the inversion symmetry [77] mono-layer electron 80 keV n/a TEM beam in vacuum removed top and bottom S atoms [78] mono-layer electron 200 keV 3000 electrons/nm 2 /s TEM beam in vacuum created S vacancies, increased electric resistance [79] mono-layer electron 15 keV 280 µC/cm 2 EBL in vacuum produced local strain and changed band structure [80] mono-layer electron 80 keV 40 A/cm 2 TEM beam in vacuum produced holes and Mo 5 S 3 nanoribbons [81] amorphous 5-7 layer electron 1 keV 1-10 min EBI in vacuum crystallized [82] mono-layer U 238 1.14 GeV 4000 ions/cm 2 heavy ion accelerator in vacuum total damaged [83] micron thickness Ar + 500 eV 2.26 × 10 15 ions/cm 2 plasma UHV produced S vacancies [84] bi-layer Ar + 500 eV 10 14 -10 15 ions/cm 2 plasma UHV produced S vacancies and MoS 6 vacancy clusters [84] mono-layer Ar + 500 eV 2.26 × 10 15 ions/cm 2 plasma UHV damaged [84] 200 µm thickness proton 3.5 MeV 5 × 10 18 ions/cm 2 Singletron facility RT preserved lattice structure, produced defects, changed magnetic moments [85] few-layer proton 10 MeV 10 12 -10 14 ions/cm 2 MC-50 cyclotron n/a decreased electrical conductance [86] mono-layer proton 100 keV 10 12 -10 15 particles/cm 2 LEAF n/a created defects [87] bi-layer proton 100 keV 6 × 10 14 particles/cm 2 LEAF n/a created defects [87] bulk He 2+ 1.66 MeV 900 MGy ion accelerator n/a changed Raman scattering slightly [88] nanosheet He 2+ 1.66 MeV 900 MGy ion accelerator n/a invariant [88] few-layer He 2+ 30 keV 10 18 ions/cm 2 FIB beam in vacuum milled or damaged [89] mono-layer He 2+ 3.04 MeV 8 × 10 13 particles/cm 2 PTA n/a produced defects [90] mono-layer He + 30 keV 10 12 -10 16 ions/cm 2 HIM in vacuum produced S vacancies [91] mono-layer He + 30 keV 10 13 -10 17 ions/cm 2 NFM in vacuum ...…”
Section: Irradiated Mos 2 Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to DFT calculations, the bandgap of a MoS2 monolayer shrinks with tensile strain but broadens with compressive strain (Fig. 6(a)) [88][89][90][91]. Chalcogen vacancies generally lead to compressive strain and therefore locally increase the bandgap [92].…”
Section: Local Bandgap Modificationmentioning
confidence: 99%